Câmeras de ação como um instrumento viável e confiável para realizar uma análise cinemática tridimensional em duplo meio e avaliar a assimetria da braçada no nado crawl - Gustavo Ramos Dalla Bernardina (2022)
The present study aims to evaluate the feasibility and reliability of action sport cameras as an instrument to perform 3D kinematic analysis in dual-media and to evaluate stroke symmetry in front crawl swimming. For this, the work was divided into two experiments, in which 12 action cameras positioned outside and inside the water (estimated acquisition volume of 8 x 3.5 x 3 meters) were used. In the first experiment, we evaluated the accuracy and reliability of the system through a rigid bar test, containing markers that transited between environments (air and water). Two markers fixed on the bar (dr: 500 mm) were moved continuously between the media, air and water, within the previously calibrated acquisition volume and the distance between these markers was reconstructed three-dimensionally as a function of time. The results found for 3D reconstruction accuracy (mean error less than 2 mm) in relation to the medium in which the bar was being moved suggest that no specific dependence of the error magnitude (1.2% to 0.8%) in the distribution of markers in space has been verified. Furthermore, the reliability results suggest that the system presents reproducible data with each new assembly, with EPM values of 1 millimeter and CV below 1%, indicating a low measurement variability. In the second experiment, we compared the displacement curves of the right and left arm strokes of freestyle swimming to assess asymmetry. Five male swimmers swam the 25-yard freestyle stroke at three different speeds (self-selected speed, speed corresponding to 85% of the 200-yard maximum test [T200] and speed corresponding to 100% of the T200). Markers were fixed on the distal end of the third finger of the right and left hands and in each attempt two cycles of right and left arm strokes were acquired. Through of the functional analysis of variance (FANOVA) displacement asymmetry in the Z axis was identified in the crawl swimming regardless of the exercise intensity. In conclusion, this thesis suggests that the 3D kinematic analysis system using action sport cameras for use in dual media, with a greater number of cameras and with the non-linear calibration method allowed the use of a greater volume of acquisition and showed results of high accuracy and reliability. Furthermore, the possibility of using FANOVA to identify movement regions influenced by a given experimental condition or training level can provide a contribution to the analysis and understanding of asymmetry in the Biomechanics of sport.